2011
DOI: 10.1074/jbc.m111.264325
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Protects Human Macrophages from Cellular Cholesterol Accumulation and Attenuates the Proinflammatory Response

Abstract: Cholesterol-laden monocyte-derived macrophages are phagocytic cells characteristic of early and advanced atherosclerotic lesions. Interleukin-6 (IL-6) is a macrophage secretory product that is abundantly expressed in atherosclerotic plaques but whose precise role in atherogenesis is unclear. The capacity of macrophages to clear apoptotic cells, through the efferocytosis mechanism, as well as to reduce cellular cholesterol accumulation contributes to prevent plaque progression and instability. By virtue of its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 56 publications
3
76
0
Order By: Relevance
“…IL-6 has been also demonstrated to increase the cholesterol efflux to HDL in macrophages. 10 Consequently, we hypothesized that IL-6 may modulate the transendothelial transport of HDL. Indeed, here we provide evidences that IL-6 enhances the binding and transport of HDL in an SR-BI-and ABCG1-independent way.…”
mentioning
confidence: 99%
“…IL-6 has been also demonstrated to increase the cholesterol efflux to HDL in macrophages. 10 Consequently, we hypothesized that IL-6 may modulate the transendothelial transport of HDL. Indeed, here we provide evidences that IL-6 enhances the binding and transport of HDL in an SR-BI-and ABCG1-independent way.…”
mentioning
confidence: 99%
“…IL-6 also maintains a separate anti-inflammatory and neuroprotective function through oligodendrocyte differentiation, neurotropism, and peripheral nerve regeneration mediated by the membrane-bound IL-6R on select cells such as microglia [26]. Human monocytes are directed away from differentiation into dendritic cells and toward macrophages which have increased anti-inflammatory IL-4 and IL-10 and decreased IL-1β production [27]. Given the dual roles of IL-6, it is possible the relative balance between the two pathways shifts with age.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this idea, MFG-E8 [203] and its receptor v 3/5, as well as Gas6 and its ligand MerTK [116,204] are frequently overexpressed in breast cancers. One recent study demonstrated that the protumorigenic cytokine IL-6 induces expression of MerTK, enhancing the ability of macrophages to engulf apoptotic cells and increasing production of wound healing cytokines such as IL-4 and IL-10 [205]. Recently published data implicates MerTK in breast cancer metastasis [206].…”
Section: Physiological and Pathological Consequences Of Efferocytosismentioning
confidence: 99%